Antiviral and Symptom Free Days for Confirmed Covid-19 Students - Mahmuda, Iin Novita Nurhidayati; Sifak, Sheila Faadhila (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Introduction: The limitations of health service facilities mean that Covid-19 case services are only for moderate and severe cases, while asymptomatic/mild cases are advised to selfisolate. The availability of antivirals for self-isolation patients is often limited, so the patient's recovery rate can be longer. The purpose of this study was to determine the difference in symptom-free days in Covid-19 patients who received and did not receive antivirals. Method: This type of analytic research is observational with a cross sectional approach. The research sample was 93 UMS students who were confirmed to have COVID-19 in March 2020 - August 2021. The research data was obtained by an online questionnaire. Data analysis was performed using the Mann Whitney test. Results: There were 32 self isolation Covid-19 patients who received antivirals (34.4%). In these patients, the symptom free days were 8.9 days; while the 61 patients (65.6%) who did not receive antivirals reported a symptom free day of 12.2 days. The Mann Whitney test obtained a p value = 0.023 indicating that there was a difference in symptom free days between Covid- 19 patients who received and did not receive antivirals. Conclusion: Giving antivirals to self isolation Covid-19 patients shortens symptom free days.